Responses to Salduz: procedural tradition, change and the need for effective defence - Jackson, John D. (Wiley, 2016)
This article examines the responses of national courts to the ECtHR's decision in Salduz v Turkey that suspects be provided with access to a lawyer before they are first interrogated by the police. It argues that harmonious application of human rights standards in criminal proceedings should build upon common values underpinning the procedural traditions of member states. ECtHR success in gaining acceptance for the principle of access to a lawyer during police interrogation, anchoring it in the privilege against incrimination, is contrasted with resistance towards giving the defence any active role during criminal investigations. It is argued that this resistance can be overcome by an appeal to safeguards that have long dominated the trial process. As the investigation phase increasingly determines the outcome of criminal proceedings, standards of fairness traditionally reserved for the trial process should be applied also to this phase in order to provide suspects with an effective defence.